Cervical cancer in Africa, Latin America and the Caribbean and Asia: Regional inequalities and changing trends. Issue 10 (10th August 2017) - Vaccarella, S.; Laversanne, M.; Ferlay, J.; Bray, F.
Abstract : The vast majority (86% or 453, 000 cases) of the global burden of cervical cancer occurs in Africa, Latin America and the Caribbean and Asia, where one in nine new cancer cases are of the cervix. Although the disease has become rare in high‐resource settings ( e.g ., in North America, parts of Europe, Japan) that have historically invested in effective screening programs, the patterns and trends are variable elsewhere. While favourable incidence trends have been recorded in many populations in Asia and Latin America and the Caribbean in the past decades, rising rates have been observed in sub‐Saharan African countries, where high quality incidence series are available. The challenge for countries heavily affected by the disease in these regions is to ensure resource‐dependent programmes of screening and vaccination are implemented to transform the situation, so that accelerated declines in cervical cancer are not the preserve of high‐income countries, but become the norm in all populations worldwide. Abstract : What's new? While cervical cancer burden has declined in regions with effectively implemented screening programs, the disease remains a major cause for concern in low‐resource settings. This study draws attention to Africa, Latin America and the Caribbean and Asia, where mortality rates for cervical cancer were estimated to be about half the rates observed for incidence, based on analyses of GLOBOCAN 2012 data. About 90% of cervical cancer deaths globally were found to occur in these regions. The findings highlight the importance of cervical cancer screening in low‐resource settings, where inequities in detection and prevention are heavily impacting women's health.